Differences Level of Husbands Vasectomy Knowledge with the Participation in Vasectomy Program in Karanganyar Regency - Bayu Prasetyo; Endang Sahir; Slamet Riyadi (Nexus Kedokteran Komunitas, 2015)
Background: Vasectomy is a contraception method for husbands. Based on BKBBN data in 2014, there is only 0.09% new participants that became vasectomy acceptors from total amount 7.603.194 participants. Their participation could be influenced by their knowledge of vasectomy. The aim from this research is to examine the difference level of husbands vasectomy knowledge with the participation in vasectomy program in Karanganyar Regency. Methods: It was an analytic observasional research with cross-sectional design that used 140 husband for be respondents. There were70 vasectomy acceptors and 70 non vasectomy acceptors. The data were taken from respondents by questionnaire that was tested the validity and reliability in Karanganyar Regency, Jawa Tengah Province. The data analysis in this research was tested with Chi Square Comparation Test in 19th version of SPSS for windows, p < 0,05. Results: In vasectomy acceptors group, there were 12 respondents (17,14%) with good knowledge, 52 respondents (72,29%) with average knowledge, and 6 respondents with bad knowledge. In non vasectomy acceptors group, there were 12 respondents (17,14%) with good knowledge, 53 respondents (75,72%) with average knowledge, and 5 respondents (7,14%) with bad knowledge. The X2 value of Chi Square Comparation Test were 0,100 and the significancy were 0,951 that showed no meaningfull difference level of husbands vasectomy knowledge with the participation in vasectomy program. Conclusion: There was no meaningfull difference level of husbands vasectomy knowledge with the participation in vasectomy program in Karanganyar Regency. Keywords: knowledge level, vasectomy program participation.